The Role of Type I Diabetes in Intervertebral Disc Degeneration. Issue 17 (1st September 2019) - Russo, Fabrizio; Ambrosio, Luca; Ngo, Kevin; Vadalà, Gianluca; Denaro, Vincenzo; Fan, Yong; Sowa, Gwendolyn; Kang, James D.; Vo, Nam
Abstract : Study Design: An experimental laboratory study. Objective: To investigate the pathogenesis of intervertebral disc degeneration (IDD) in a murine model of type 1 diabetes mellitus (DM), namely nonobese diabetic (NOD) mouse. Summary of Background Data: IDD is a leading contributor of low back pain, which represents one of the most disabling symptoms within the adult population. DM is a chronic metabolic disease currently affecting one in 10 adults in the United States. It is associated with an increased risk of developing IDD, but the underlying process remains poorly understood. Methods: Total disc glycosaminoglycan content, proteoglycan synthesis, aggrecan fragmentation, glucose transporter gene expression, and apoptosis were assessed in NOD mice and wild-type euglycemic control mice. Spinal structural and molecular changes were analyzed by micro-computed tomography, histological staining (Safranin-O and fast green), and quantitative immunofluorescence (anti-ADAMTS-4 and -5 antibodies). Results: Compared with euglycemic controls, NOD mice showed increased disc apoptosis and matrix aggrecan fragmentation. Disc glycosaminoglycan content and histological features of NOD mice did not significantly differ from those of euglycemic littermates. Conclusion: These data demonstrate that DM may contribute to IDD by increasing aggrecan degradation and promoting cell apoptosis, which may represent early indicators of the involvement of DM in the pathogenesis of IDD. Level of Evidence: N/A Abstract : Intervertebral disc degeneration is often associated with diabetes mellitus, although the biological basis of such a link is poorly understood. We analyzed biochemical and morphological changes in the discs of nonobese diabetic mice compared with euglycemic littermates. Diabetic mice showed an increased disc cell apoptosis and matrix breakdown.